Synthesis and Characterization of Core–Shell Magnetic Nanoparticles NiFe2O4@Au - Diana Saykova; Svetlana Saikova; Yuri Mikhlin; Marina Panteleeva; Ruslan Ivantsov; Elena Belova (Metals, 2020)
In this study, NiFe2O4@Au core–shell nanoparticles were prepared by the direct reduction of gold on the magnetic surface using amino acid methionine as a reducer and a stabilizing agent simultaneously. The obtained nanoparticles after three steps of gold deposition had an average size of about 120 nm. The analysis of particles was performed by X-ray diffraction, transmission electron microscopy, X-ray photoelectron spectroscopy, and UV-Vis spectroscopy techniques. The results indicate successful synthesis of core–shell particles with the magnetic core, which consists of a few agglomerated nickel ferrite crystals with an average size 25.2 ± 2.0 nm, and the thick gold shell consists of fused Au0 nanoparticles (NPs). Magnetic properties of the obtained nanoparticles were examined with magnetic circular dichroism. It was shown that the magnetic behavior of NiFe2O4@Au NPs is typical for superparamagnetic NPs and corresponds to that for NiFe2O4 NPs without a gold shell. The results indicate the successful synthesis of core–shell particles with the magnetic nickel ferrite core and thick gold shell, and open the potential for the application of the investigated hybrid nanoparticles in hyperthermia, targeted drug delivery, magnetic resonance imaging, or cell separation. The developed synthesis strategy can be extended to other metal ferrites and iron oxides.